No longer 'perceived as naughty…'. (2nd August 2022) - Hogg, Sally
Abstract : Early relationships should not just be an interesting part of undergraduate degrees. They should be taught to all professionals as a tool to change the future. This opinion piece begins to look at early relationships and early trauma, practitioners' awareness and what can be done differently.